Diversity of a Large Collection of Natural Populations of Mango (Mangifera indica Linn.) Revealed by Agro-Morphological and Quality Traits - Cuixian Zhang; Dehong Xie; Tianqi Bai; Xinping Luo; Faming Zhang; Zhangguang Ni; Yufu Chen (Diversity, 2020)
Collection, characterization and utilization of genetic resources are crucial for developing varieties to meet current and future needs. Although mango is an economically important fruit tree, its genetic resources are still undocumented and are threatened in their natural habits. In this study, the variability of 452 mango accessions from three regions in China (Nujiang, Lancang river and Honghe) was assessed using 41 descriptors including qualitative and quantitative traits, with the aim to identify mango accessions with excellent agronomic and quality traits. To this end, descriptive and multivariate analyses were performed. Based on Shannon−Weaver diversity index, qualitative traits including pericarp color, fruit aroma, flesh color, and fruit flavor recorded the highest variability in the germplasm. Fruit related traits including pulp weight, peel weight, and fruit weight were the most diverse traits in the germplasm with a high coefficient of variation (CV > 40%). Significant differences (MANOVA test, p < 0.000) were observed among the three regions for most of the quantitative traits. Biologically significant and positive correlations were found among agronomically important traits such as fruit weight and pulp weight, fruit weight and edible rate. The hierarchical cluster analysis revealed tree clusters, indicating a low diversity in the germplasm. The majority of the descriptors contributed to the differentiation of the accessions. Accessions with good fruits quality (high fruit weight, pulp weight, and edible rate) were found in Cluster 2. Accessions in this cluster could be used for fruit quality improvement in mango breeding programs. Our study sheds light on the diversity of a large collection of natural mango population in China and provides relevant information for efficient conservation and harnessing of mango genetic resources.